Espaço da festa de Nossa Senhora do Rosário da cidade de Monte do Carmo – TO: A Rainha do Rosário - Avelino, Ducinária Azevedo (Universidade Federal do Tocantins, 2022)
This research deals with the historical aspects of the celebration of Nossa Senhora do Rosário in the city of Monte do Carmo, State of Tocantins. The dynamics created for this festivity and the protagonists (residents) who carry out the festival, who are responsible for the secular maintenance of the tradition, justifying the research and highlighting the importance of the festival for the community and for the city. The objective of the research is to analyze the sacred space of the feast of Nossa Senhora do Rosário, having as methodological procedures the direct observation, while resident and participant of the feast, and a bibliographical review available. It is necessary to reflect on the importance of the festival for the community, realizing the specifics of the cultural environment and the geographic space in which the festival takes place. It is concluded that the territory covered by the participants and faithful in the city, becomes a sacred space as the festival lasts, where rituals and acts of devotion and faith take place, which also characterize a cultural dimension of Monte do Carmo.